Selection odds in talent selection among female handball players by relative age, biological maturity, body size, and body composition - Tróznai, Zs.; Utczás, K.; Pápai, J.; Pálinkás, G.; Szabó, T.; Petridis, L. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
INTRODUCTION: Selecting talented players is a common practice in youth sports. However, it is widely recognised that selection may be biased by variations in relative age or maturation, which in turn may result in differences in body size and muscular development. Previous research has suggested that talent selection should include technical tasks instead of body size and physical test measurements potentially reducing in this way the impact of the relative age effects and maturation. In this study we examined a single national female adolescent handball selection process, which was based only on sport-specific technical tasks exploring the effects of relative age, biological age, body size, body composition and maturity status on the selection. METHODS: Measurements were performed in a sample of n=530 female handball adolescent players (aged 13-14 years). Participants went through anthropometric, body composition, and bone age measurements and then performed the selection tasks. Body mass and body composition were assessed using inBody 720, biological maturity was estimated based on bone age using an ultrasound-based device. The selection program consisted of three selection stages including handball-specific skills and in-game performance as selection criteria. Binary logistic regression was used to examine the effects of body size, body composition, and biological age (predictors) on the selection (dependent variable). The odds of selection (0=not-selected, 1=selected) were examined in separate models according to body size (body height and body mass), body composition (skeletal muscle mass and percent body fat), and developmental status (maturity status and relative age). RESULTS: At the first selection stage, the explanatory power of the regression models was significant for the developmental status (9.6%) and body composition (8.0%), but not for body size. At the regional stage, all three models were significant, however the explanatory power remained rather small (15.1%, 13.0%, and 10% respectively). At the national stage, only developmental status (15.2%) had a significant effect on the selection. At the regional stage, larger body height increased selection odds by about 12%, larger muscle mass by 25%, whereas larger percent body fat decreased selection odds by 7%. The largest odds were found for relative age with larger age increasing selection odds by 3.5-4 times, while more advanced biological maturity by 1.8 times. CONCLUSION: Regression results suggest that the examined variables may have a significant effect on the selection, but their explanatory power is rather limited indicating that additional factors may account in the selection process. The developmental status was the strongest predictor in the selection, but it seems that the impact of relative age and maturation is not limited to body size and muscular development, but it may expand to other important aspects in handball, such as technical competence or game intelligence.